QIṢṢAH QAṢĪRAH JIDDAN: SEBUAH GENRE TERBARU DALAM SASTRA ARAB - Tasnimah, Tatik Mariyatut (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
This article aims to describe the development of contemporary Arabic literary genre called Qişşah Qaşīrah Jiddan (QQJ), by revealing its characteristics, its components, and the factors that influence its emergence. This research fills the gap in the study of QQJ, in terms of both theory and application, despite the fact that it has existed among classic genres. To fulfill its objectives, this research uses descriptive analysis by examining the production of the literary works, its existence, its role and social reality. To explore the connection between QQJ and the social reality that surrounds it, this research applies qualitative methods by studying the documents that focus on contextual analysis of written materials. Based on the analysis, this study found that the emergence of the QQJ genre in the repertoire of contemporary Arabic literature is a response to the demands and needs of this fast-paced technological era which requires something practical and pragmatic. Though this narrative genre stems from short story, it is neither an advancement of a short story, nor the development of its branches or the incarnation of the old Arabic literary genre. Instead, it is an autonomous genre that adopts a variety of things in its development, especially aspects underlying postmodernity such as being practical, dynamic, and digital.